Bibliographic reviews as an element of similarity between journals. Analysis of the category Communication in Web of Science - Repiso, Rafael; de Aguilera, Miguel; Castillo Esparcia, Antonio (Revista General de Información y Documentación, 2019)
This paper analyses the Book Reviews published in Communication journals indexed in the category Social Science Citation Index (WoS) in the period 2013-2017. Through the co-presence of the same works reviewed in different journals, the aim is to study the relationship of similarity between journals in the area. The results show how 25 journals do not publish reviews, analyzing 63 journals, which allows to study the individual similarity of journals and at the same time generate area maps. The methodological proposal is valid but limited. The results in the area of Communication are logical, grouping the journals by defined topics. Using bibliographic reviews as an element of similarity between journals should in any case be complementary to other methods and will be especially significant in areas of Humanities, where books are the object of study.